2015
DOI: 10.3928/01477447-20151020-02
|View full text |Cite
|
Sign up to set email alerts
|

Gait Analysis Using a Support Vector Machine for Lumbar Spinal Stenosis

Abstract: Lumbar spinal canal stenosis (LSS) is diagnosed based on physical examination and radiological documentation of lumbar spinal canal narrowing. Differential diagnosis of the level of lumbar radiculopathy is difficult in multilevel spinal stenosis. Therefore, the authors focused on gait analysis as a classification method to improve diagnostic accuracy. The goal of this study was to identify gait characteristics of L4 and L5 radiculopathy in patients with LSS and to classify L4 and L5 radiculopathy using a suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
(24 reference statements)
4
15
0
Order By: Relevance
“…However, only a few studies involving ML techniques to investigate spinal disorders have been presented so far; this lack of documentation reflects the technical difficulties in assessing position and motion of the vertebrae due to soft tissue artifacts . An example of a pioneering study in this field is offered by Hayashi et al, who trained an SVM to distinguish gait patterns associated to either L4 or L5 radiculopathy in patients suffering from lumbar canal stenosis, achieving an accuracy of 80.4%.…”
Section: Applications Of Ai and ML In Spine Researchmentioning
confidence: 99%
“…However, only a few studies involving ML techniques to investigate spinal disorders have been presented so far; this lack of documentation reflects the technical difficulties in assessing position and motion of the vertebrae due to soft tissue artifacts . An example of a pioneering study in this field is offered by Hayashi et al, who trained an SVM to distinguish gait patterns associated to either L4 or L5 radiculopathy in patients suffering from lumbar canal stenosis, achieving an accuracy of 80.4%.…”
Section: Applications Of Ai and ML In Spine Researchmentioning
confidence: 99%
“…FPA referred to the angle between the longitudinal axis of one foot and the walking direction, and its outward rotation indicated that the patient had an "out-toe" gait when walking [24]. Previous studies confirmed that patients with LSS had a wide-based gait [17], which was mainly manifested by awkward and faltering walking patterns. These patterns could reflect the characteristics of patients with unstable trunk and limited dynamic balance [11].…”
Section: Discussionmentioning
confidence: 99%
“…SVM classifier is computationally very efficient and has been used extensively in gait identification [32,33].A leave-one-out-cross- statistically using the independent t-test in SPSS software [34].For each classification accuracy a symmetrical 95% confidence interval (CI) was calculated assuming binomial distribution. …”
Section: Feature Extraction Normalization Representation and Classimentioning
confidence: 99%